An experimental study of two grave excavation methods: Arbitrary Level Excavation and Stratigraphic Excavation. Issue 2 (12th December 2016) - Evis, Laura Helen; Hanson, Ian; Cheetham, Paul Nicholas
Abstract: The process of archaeological excavation is one of destruction. It normally provides archaeologists with a singular opportunity to recognise, define, extract and record archaeological evidence: the artefacts, features and deposits present in the archaeological record. It is expected that when archaeologists are excavating in a research, commercial or forensic setting the methods that they utilise will ensure a high rate of evidence recognition and recovery. Methods need to be accepted amongst the archaeological and scientific community they are serving and be deemed reliable. For example, in forensic contexts, methods need to conform to scientific and legal criteria so that the evidence retrieved is admissible in a court of law. Two standard methods of grave excavation were examined in this study with the aim of identifying the better approach in terms of evidence recovery. Four archaeologists with a range of experience each excavated two similarly constructed experimental 'single graves' using two different excavation methods. Those tested were the arbitrary level excavation method and the stratigraphic excavation method . The results from the excavations were used to compare recovery rates for varying forms of evidence placed within the graves. The stratigraphic excavation method resulted in higher rates of recovery for all evidence types, with an average of 71% of evidence being recovered, whereas the arbitrary level excavation method recovered an average of 56%. Neither method recovered all of the evidence. These findings raise questions about the reliability and so suitability of these established approaches to excavation.